(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2008)
High-resolution quantitative and qualitative analyses of the planktonic foraminifer and calcareous nannofossil content have been carried out on three Middle Miocene sections, from the Mediterranean area. Such sections (Cretaccio section, Tremiti Islands, Southern Italy; Moria section, Marche Region, Central Italy; DSDP Site 372 succession, Balearic Basin), all well known in the literature, have been chosen because of their high-quality biostratigraphic potential. Remarkable magnetostratigraphic data were provided by the Site 372 succession where all chrons and subchrons of the interval C5Br-C5AAn have been recognised. The investigated interval falls between the First Occurrence (FO) of Praeorbulina glomerosa sicana and the Last Occurrence (LO) of Sphenolithus heteromorphus and Globorotalia peripheroronda. The LO of S. heteromorphus was detected in the uppermost part of the investigated sequence of Site 372 at the same stratigraphic level of the G. peripheroronda LO. A drastic decrease in abundance of S. heteromorphus (Last Common Occurrence -LCO) was detected slightly below its last occurrence; this event is well correlatable with the same event astronomically calibrated at Ras-il Pellegrin section (Malta Island), which has been recently ratified as the Global Stratotype Section and Point (GSSP) for the base of the Serravallian by the International Union of Geological Sciences. The stratigraphic correlation of the studied sections is based on first and last occurrences, abundance fluctuations of selected taxa and additional biohorizons. In particular the peculiar distribution pattern of some taxa, e.g. Paragloborotalia siakensis and Helicosphaera waltrans, offered the opportunity to increase the biostratigraphic resolution of the Langhian interval. The resulting integrated calcareous plankton bio-magnetostratigraphic scheme represents the downward extension of that one previously established for the Serravallian-Tortonian interval. The biostratigraphic correlation of the studied sections with the Langhian historical Stratotype pointed out its low degree of reliability. On the other hand, none of the sections here studied is suitable to be proposed as candidate for defining the Langhian GSSP. Thus the problem of finding, in the Mediterranean area, a valid section which could yield a new GSSP for the Langhian Stage is still open.